The Impact of Electronic Disclosure Using Extensible Business Reporting Language (XBRL) on Share Price: Trading Volume As a Mediating Variable - Mohammad Al-Zoubi, Abdullah; Suliman Al-Tahat, Saqer; Salem Almasae, Ibtisam (Jordan Journal of Business Administration, 2025)
This study aimed to analyse the impact of electronic disclosure through eXtensible Business Reporting Language (XBRL) on the share price of banks listed in the Amman Stock Exchange and assess the role of trading volume as a mediating variable in this context. The study population comprised all banks listed in the Amman Stock Exchange, totalling 14 banks, all of which selected as the study sample due to the small size of the statistical population. Data was collected from the Amman Stock Exchange website every quarter for the period from 2019 to 2022, covering two phases: the first phase, electronic disclosure of financial statements before the use of XBRL from 2019 to 2020, and the second phase, electronic disclosure of financial statements after the adoption of XBRL from 2021 to 2022. The analysis utilized the Baron and Kenny (1986) model, which applied simple and multiple regression testing, and the Andrew F. Hayes model to test the total, direct, and indirect effects using the Hayes Process Macro program. The study concluded that electronic disclosure using XBRL impacts the share price through trading volume as a mediating variable and that the mediation is partial, meaning that trading volume as a mediating variable partially mediates the effect of electronic disclosure using XBRL on the share price. Therefore, the study recommends the continued enforcement by the Amman Stock Exchange of banks’ use of XBRL in disclosing their financial statements and conducting future studies related to it, given its recent implementation in Jordan.